TEKNIK MENYUSUI YANG BENAR PADA IBU MENYUSUI STUDI DI BPS.UMI MUNTADIROH S,ST.MKES MOJOKERTO - Yuliani, Farida (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
Breastmilk and breastfeeding have great benefits for both baby and for mom. Not infrequently the failure in feeding still occur. This is usually caused by technical and nursing positions are not appropriate, not because her milk production is less. Techniques andinappropriate position during breastfeeding because mothers lack knowledge about correctbreastfeeding technique. So the aim for this study was to indentify the breast feeding technique that used by mother. This research used a descriptive design by using 36 responden as sample in BPS Umi Muntadiroh. The result showed that 2 respondents (5,55%) have good technique and only 3 respondents have bad technique and the others is have technique in enough degrees. Mothers who have experienced breastfeeding because it has had a lot of children will tend to have good knowledge about breastfeeding techniques. A health workerwho engaged in the field of lactation, should know that although breastfeeding is a natural process, but necessary to achieve successful breastfeeding knowledge about breastfeeding techniques are correct. So that should be as a midwife should always provide information and guide for nursing mothers to perform breast-feeding techniques appropriately so that the baby's nutritional needs are met.Keyword: breast feeding, mothers.